Global aging - the nature of longevity risk - Trzpiot, Grażyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In this paper we investigate the latest developments on longevity risk modelling. We first introduce longevity risk to allow for a better understanding of the related challenges in term of risk management from both a financial and insurance point of view. The article also provides a global view on the practical issues of longevity. Simultaneously, the development on the longevity has enhanced the need of capital markets as to manage and transfer the risk. Therefore, we also highlight future developments on longevity risk management from a financial point of view.